Ekstraksi DNA Phytophthora palmivora Isolat Kelapa - Achmadi Priyatmojo; Siti Subandiyah (Jurnal Perlindungan Tanaman Indonesia, 1996)
Coconut isolate of Phytophthora palmivora DNA was extracted from sporangium and mycelium using SDS and Proteinase-K method. Sporangium and mycelium were harvested from liquid and solid culture of Potato Dextrose medium. The result of the study showed that the DNA extracted from sporangium and mycelium of 8 days solid culture was seen as distinct band. On the other hand, the dNA from sporangium and mycelium of 24 days old liquid culture was fragmented with smear band appearance.